The Role of Rape-Supportive Attitudes, Alcohol, and Sexual Arousal in Sexual (Mis)Perception: An Experimental Study - Benbouriche, Massil; Testé, Benoit; Guay, Jean-Pierre; Lavoie, Marc E. (Journal of Sex Research, 2019)
While sexual misperception does not irrevocably lead to sexual aggression, it remains a significant risk factor. The present study investigated the effects of rape-supportive attitudes, alcohol, and sexual arousal on sexual perception. We used a 2 × 2 between-participants factorial design to randomly assign 135 men from the general population to a condition with or without alcohol (blood alcohol concentration target of .08%) and to a condition with or without sexual arousal. Participants were asked to listen to an audiotape depicting a sexual interaction between a man and woman and to indicate if and when they believed the woman was no longer interested in having sex. Results, obtained through survival analyses, indicate that the effects of rape-supportive attitudes on sexual misperception are moderated by alcohol consumption. Alcohol appears to be an important situational factor for activating men's implicit theories. Our study sheds new light on the role of knowledge structures in sexual perception: It identifies when, as well as suggesting how, rape-supportive attitudes may disturb sexual perception and ultimately lead to sexual misperception.
Keywords: Adult; Alcohol Drinking; Arousal; Attitude; Female; Humans; Male; Rape; Refusal to Participate; Sexual Behavior; Survival Analysis; Tape Recording; Young Adult

Experiences and perceptions of gender in the Australian music industry - Fairlamb, Hannah Mary; Fileborn, Bianca (Perfect Beat, 2019)
This article reports results from an online survey (n=207) about experiences and perceptions of gender from those working in the Australian music industry. Taking a feminist approach, theory on gender and hegemonic masculinity is used to discuss power in a gendered context in this industry. Literature shows women and girls experience a range of difficulties in the music industry worldwide, such as negative assumptions about their skill levels. The small body of research on gender and the Australian music industry has discussed topics such as the forgetting of women in Australian popular music history. Results reported in this article show that women’s worst experiences most often related to sexual violence or unwanted sexual advances; and men’s most often related to money. Findings contribute to the field by providing gendered analysis of self-reported data in an under-researched industry.
Keywords: Australia; gender; music; music industry; popular music; sexual harassment

Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events - Fileborn, B.; Wadds, P.; Barnes, A. (2019)
Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events
Keywords: Camille

Safety, sexual harassment and assault at Australian music festivals: final report - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (2019)
Keywords: Camille

Bar Training for Active Bystanders: Evaluation of a Community-Based Bystander Intervention Program - Powers, Ráchael A.; Leili, Jennifer (Violence Against Women, 2018)
Bystander intervention programs are proliferating on college campuses and are slowly gaining momentum as sexual violence prevention programs suitable for the larger community. In particular, bystander intervention programs aimed at bar staff have been developed in a number of locations. This study entails the exploratory evaluation of a community-based bystander program for bar staff. Using a pre–posttest design, this study suggests that evidence surrounding the effectiveness of this program is promising as it decreases rape myths, decreases barriers to intervention, and increases bartenders willingness to intervene. Future research and policy implications are discussed.
Keywords: Camille

When Women Do Not Want It: Young Female Bargoers’ Experiences With and Responses to Sexual Harassment in Social Drinking Contexts - Graham, Kathryn; Bernards, Sharon; Abbey, Antonia; Dumas, Tara M.; Wells, Samantha (Violence Against Women, 2017)
Women frequently experience unwanted sexual touching and persistent advances at bars and parties. This study explored women?s responses to these unwanted experiences through online surveys completed by 153 female bargoers (aged 19-29) randomly recruited from a bar district. More than 75% had experienced sexual touching or persistence (46% both). Most women used multiple deterrent strategies, including evasion, facial expressions, direct refusals, aggression, friends? help, and leaving the premises. Women experienced negative feelings (disrespected, violated, disgusted, angry, embarrassed), especially from incidents involving touching. Cultural change is needed to reduce substantial negative impacts of sexual harassment on women in drinking and other settings.

Montréal une ville festive pour toutes: Avis sur la sécurité des femmes et des jeunes femmes cisgenre et trans lors des événements extérieurs à Montréal - Conseil des Montréalaises (2017)
Keywords: Bibliographie; Camille; Nettoyer

‘Staff can't be the ones that play judge and jury’: Young adults’ suggestions for preventing unwanted sexual attention in pubs and clubs - Fileborn, Bianca (Australian & New Zealand Journal of Criminology, 2017)
This paper explores young adults' suggestions for preventing unwanted sexual attention in licensed venues. Despite emerging evidence that unwanted sexual attention and sexual violence are significant issues faced by young adults in the night-time economy, there has been little introduced in the way of preventative strategies or campaigns. Drawing on a mixed-methods research project undertaken in Melbourne, Australia, I contend that exploring young adults' suggestions for prevention is instructive in a number of ways. Young adults are the primary users of licensed venues and thus may provide insight into potential strategies for prevention. It can also illuminate the discursive positions that young adults draw on in talking about prevention and their understandings of unwanted sexual attention.
Keywords: Camille

Doing gender, doing safety? Young adults’ production of safety on a night out - Fileborn, Bianca (Gender, Place & Culture, 2016)
This article explores the ways in which young adults produce a sense of safety in pubs and clubs. Despite considerable anxiety around issues pertaining to safety and violence in the night-time economy, there is little consideration of how young adults themselves feel about their safety on a night out, or how they achieve a sense of safety in a seemingly ‘risky’ social space. Drawing on mixed-methods research conducted in Melbourne, Australia, in this article I consider the strategies that young adults used to feel safe on a night out. I argue that feeling ‘safe’ is something that is actively produced through the use of these strategies, as well as providing an avenue for ‘doing’ gender.
Keywords: Camille; Safety; Seguridad; economía nocturna; feminidad; femininity; gender performance; licensed venues; locales autorizados; masculinidad; masculinity; night-time economy; performance de género; 夜间经济; 女性气质; 安全; 性别展演; 拥有许可证之营业场所; 男性气概

Reclaiming the Night-Time Economy - Fileborn, Bianca (Palgrave Macmillan UK, 2016)
Keywords: Alcohol; Assemblage; Camille; Community; Crime prevention; Criminology; Culture; Drugs; Environmental design; Gender; LGBTIQ; Licensed venues; Safety; Sexual consent; Sexual ethics; Sexual offending; Sexual violence; Sexuality; Space; Young people

"Yeah, We Serve Alcohol, but … We Are Here to Help": A Qualitative Analysis of Bar Staff's Perceptions of Sexual Violence - Powers, Ráchael A.; Leili, Jennifer (Violence and Victims, 2016)
This study is an exploratory analysis of how bar staff perceive their role in preventing sexual harassment and assault. In particular, through qualitative focus group interviews, this study explores bar staff's attitudes surrounding sexual harassment/assault, how they currently handle these situations, and their opinions regarding programs and policies that currently mandate responsibility. Six major themes emerged including their hesitation to discuss sexual violence, their unique position as a service provider, their lack of knowledge (but eagerness to learn), and their reliance on stereotypical scenarios of sexual violence and interventions. These findings are situated in a framework for understanding barriers to bystander intervention and implications for community-based bystander programs are discussed.
Keywords: Adult; Camille; Female; Focus Groups; Helping Behavior; Humans; Interpersonal Relations; Male; Rape; Restaurants; Sex Offenses

Unwanted Sexual Attention in Licensed Venues: Considering LGBTIQ Young Adults' Experiences and Perceptions - Fileborn, Bianca (2015)
English Abstract: Sexual violence within the lesbian, gay, bisexual, transgender/transsexual, intersex and queer (LGBTIQ) communities remains largely under-researched and under-theorised. Yet, emerging research suggests that sexual violence is a significant issue within the LGBTIQ communities. Additionally, the occurrence of sexual violence and unwanted sexual attention within specific social and cultural contexts is, for the most part, insufficiently examined. This article draws on research exploring young LGBTIQ adults’ perceptions and experiences of unwanted sexual attention in licensed venues. Firstly, I consider the theoretical and conceptual underpinnings of ‘unwanted sexual attention’ as a category of analysis. I then move on to consider participants’ use of licensed venues, the particular significance of pubs and clubs to LGBTIQ young people, and their perceptions and experiences of unwanted sexual attention. Finally, I discuss the implications of these findings for theoretical and conceptual understandings of unwanted sexual attention and sexual violence.
Keywords: Camille; Gender; Género; LGBTIQ; economía nocturna; licensed venues; locales con licencia; night time economy; orientación sexual; sexual orientation; sexual violence; violencia sexual

“Blurred Lines?” Sexual Aggression and Barroom Culture - Graham, Kathryn; Bernards, Sharon; Osgood, D. Wayne; Abbey, Antonia; Parks, Michael; Flynn, Andrea; Dumas, Tara; Wells, Samantha (Alcoholism, clinical and experimental research, 2014)
Background Meeting potential sexual/romantic partners for mutual pleasure is one of the main reasons young adults go to bars. However, not all sexual contacts are positive and consensual, and aggression related to sexual advances is a common experience. Sometimes such aggression is related to misperceptions in making and receiving sexual advances while other times aggression reflects intentional harassment or other sexually aggressive acts. The present study uses objective observational research to assess quantitatively gender of initiators and targets and the extent that sexual aggression involves intentional aggression by the initiator, the nature of responses by targets, and the role of third parties and intoxication. Methods We analyzed 258 aggressive incidents involving sexual advances observed as part of a larger study on aggression in large capacity bars and clubs, using variables collected as part of the original research (gender, intoxication, intent) and variables coded from narrative descriptions (invasiveness, persistence, targets’ responses, role of third parties). Hierarchical Linear Modeling (HLM) analyses were used to account for nesting on incidents in evening and bars. Results 90% of incidents involved male initiators and female targets, with almost all incidents involving intentional or probably intentional aggression. Targets mostly responded nonaggressively, usually using evasion to end the incident. Staff rarely intervened; patron third parties intervened in 21% of incidents, usually to help the target but sometimes to encourage the initiator. Initiators’ level of invasiveness was related to intoxication of the targets but not their own intoxication, suggesting intoxicated women were being targeted. Conclusions Sexual aggression is a major problem in bars often reflecting intentional sexual invasiveness and unwanted persistence rather than misperceptions in sexual advances. Prevention needs to focus on addressing masculinity norms of male patrons and staff that support sexual aggression and better management of the highly sexualized and sexist environments of most bars.
Keywords: Camille

Accounting for Space, Place and Identity: GLBTIQ Young Adults’ Experiences and Understandings of Unwanted Sexual Attention in Clubs and Pubs - Fileborn, Bianca (Critical Criminology, 2014)
This article considers the role of space, place and identity in influencing gay, lesbian, bisexual, transgender/transsexual, intersex and queer (GLBTIQ) young adults’ experiences of unwanted sexual attention in licensed venues. It is argued in this article that the roles of space, place and identity are largely absent from theoretical understandings of sexual violence. Gender-based accounts of sexual violence, while important, are unable to fully account for sexual violence that is perpetrated within and against GLBTIQ communities. Drawing on data obtained through a mixed-methods study, in the first half of the article I establish the manner in which GLBTIQ young adults’ unique relationship with licensed venues appears to mediate the ways in which unwanted sexual attention occurring in these spaces is experienced and understood. The second half of this article is concerned with exploring the intersections between unwanted sexual attention and heterosexist violence and abuse in clubs and pubs. I conclude by considering the implications of these findings for theoretical understandings of sexual violence and unwanted sexual attention.
Keywords: Gender Identity; Intimate Partner Violence; Sexual Identity; Sexual Orientation; Sexual Violence

Sex and the City: Exploring Young Women's Perceptions and Experiences of Unwanted Sexual Attention in Licensed Venues - Fileborn, Bianca (Current Issues in Criminal Justice, 2012)
Recent research has highlighted the need to explore how specific social contexts influence the occurrence of sexual violence and sexually harassing behaviours. This article considers the occurrence of unwanted sexual attention towards young women within the social context of licensed venues in Melbourne, Victoria. Using focus group data from a small qualitative study, three ‘characteristics’ of unwanted sexual attention are considered: the forms this behaviour takes and how it impacts young women; the nature of the relationship between victim and perpetrator; and the role of venue culture in facilitating this behaviour. It is argued throughout this article that an intersection of broader social norms and the specific social norms and cultural mores of licensed venues creates a social environment that can facilitate the occurrence of unwanted sexual attention, and that restrains the ways in which young women are able to respond to these experiences.
Keywords: Camille

“Yes, I Do but Not with You”: Qualitative Analyses of Sexual/romantic Overture-Related Aggression in Bars and Clubs - Graham, Kathryn; Wells, Samantha; Bernards, Sharon; Dennison, Susan (Contemporary Drug Problems, 2010)
Assaultive and aggressive behaviors related to sexual overtures are common in commercial drinking establishments (bars, pubs, and clubs). In this article, we examined the thematic content of 251 incidents of verbal and physical aggression related to sexual/romantic overtures documented by researcher-observers in a study of Toronto bars and clubs. Aggression was examined as it emerged in the following stages of the social interaction process: (a) sexual/romantic overtures that began aggressively; (b) initiators of sexual/romantic overtures who became aggressive later in the social interaction process; (c) aggression by targets of overtures; and (d) aggression by third parties. From these thematic analyses we identify the distinctions between predatory and genuine overtures and explore the potential role of the effects of alcohol.